Trends in incidence of thick, thin and in situ melanoma in Europe. (March 2018) - Sacchetto, L.; Zanetti, R.; Comber, H.; Bouchardy, C.; Brewster, D.H.; Broganelli, P.; Chirlaque, M.D.; Coza, D.; Galceran, J.; Gavin, A.; Hackl, M.; Katalinic, A.; et al.
Abstract: Background: We analysed trends in incidence for in situ and invasive melanoma in some European countries during the period 1995–2012, stratifying for lesion thickness. Material and methods: Individual anonymised data from population-based European cancer registries (CRs) were collected and combined in a common database, including information on age, sex, year of diagnosis, histological type, tumour location, behaviour (invasive, in situ ) and lesion thickness. Mortality data were retrieved from the publicly available World Health Organization database. Results: Our database covered a population of over 117 million inhabitants and included about 415, 000 skin lesions, recorded by 18 European CRs (7 of them with national coverage). During the 1995–2012 period, we observed a statistically significant increase in incidence for both invasive (average annual percent change (AAPC) 4.0% men; 3.0% women) and in situ (AAPC 7.7% men; 6.2% women) cases. Discussion: The increase in invasive lesions seemed mainly driven by thin melanomas (AAPC 10% men; 8.3% women). The incidence of thick melanomas also increased, although more slowly in recent years. Correction for lesions of unknown thickness enhanced the differences between thin and thick cases and flattened the trends. Incidence trends varied considerably across registries, but only Netherlands presented a marked increase above the boundaries of a funnel plot that weighted estimates by their precision. Mortality from invasive melanoma has continued to increase in Norway, Iceland (but only for elder people), the Netherlands and Slovenia. Highlights: This study is the most recent analysis of melanoma trends in Europe by lesion thickness. We analysed about 415, 000 cases incident between 1995 and 2012 from 13 European countries. Results showed that the incidence of invasive melanoma continues to increase, mainly due to thin lesions. There was a large variation in trends among countries, with the greatest increase in the Netherlands. Mortality from invasive melanoma continued to increase in some countries.